Introduction of Human Flt3-L and GM-CSF into Humanized Mice Enhances the Reconstitution and Maturation of Myeloid Dendritic Cells and the Development of Foxp3+CD4+ T Cells - Iwabuchi, Ryutaro; Ikeno, Shota; Kobayashi-Ishihara, Mie; Takeyama, Haruko; Ato, Manabu; Tsunetsugu-Yokota, Yasuko; Terahara, Kazutaka (Frontiers in Immunology, 2018)
Two cytokines, fms-related tyrosine kinase 3 ligand (Flt3-L) and granulocyte-macrophage colony-stimulating factor (GM-CSF), are considered to be the essential regulators of dendritic cell (DC) development in vivo. However, the combined effect of Flt3-L and GM-CSF on human DCs has not been evaluated in vivo. In this study, we therefore aimed at evaluating this using a humanized mouse model. Humanized NOD/SCID/Jak3null (hNOJ) mice were constructed by transplanting hematopoietic stem cells from human umbilical cord blood into newborn NOJ mice, and in vivo transfection (IVT) was performed by hydrodynamic injection-mediated gene delivery using plasmids encoding human Flt3-L and GM-CSF. Following IVT, Flt3-L and GM-CSF were successfully induced in hNOJ mice. At 10 days post-IVT, we found, in the spleen, that treatment with both Flt3-L and GM-CSF enhanced the reconstitution of two myeloid DC subsets, CD14-CD1c+ conventional DCs (cDCs) and CD14-CD141+ cDCs, in addition to CD14+ monocyte-like cells expressing CD1c and/or CD141. GM-CSF alone had less effect on the reconstitution of these myeloid cell populations. By contrast, none of the cytokine treatments enhanced CD123+ plasmacytoid DC (pDC) reconstitution. Regardless of the reconstitution levels, three cell populations (CD1c+ myeloid cells, CD141+ myeloid cells, and pDCs) could be matured by treatment with cytokines, in terms of up-regulation of CD40, CD80, CD86, and CD184/CXCR4 and down-regulation of CD195/CCR5. In particular, GM-CSF contributed to up-regulation of CD80 in all these cell populations. Interestingly, we further observed that Foxp3+ cells within splenic CD4+ T cells were significantly increased in the presence of GM-CSF. Foxp3+ T cells could be subdivided into two subpopulations, CD45RA-Foxp3hi and CD45RA-Foxp3lo T cells. Whereas CD45RA-Foxp3hi T cells were increased only after treatment with GM-CSF alone, CD45RA-Foxp3lo T cells were increased only after treatment with both Flt3-L and GM-CSF. Treatment with Flt3-L alone had no effect on the number of Foxp3+ T cells. The correlation analysis demonstrated that the development of these Foxp3+ subpopulations was associated with the maturation status of DC(-like) cells. Taken together, this study provides a platform for studying the in vivo effect of Flt3-L and GM-CSF on human DCs and regulatory T cells.